The Excluded Terms of Culture: Cultural Inclusion as Spectacle. - Clements, Paul (Journal for Cultural Research, 2006)
The artistic production of particular disabled individuals and groups in the UK is presented to portray the tensions within and between the social and cultural conditions of inclusion and exclusion. To help understand, articulate and embed these terms Bourdieu’s theoretical discourse on distinction where taste and cultural capital are determined by broader socio‐economic factors, is applied and evaluated. A Foucauldian analysis is also utilised to illustrate how the arts represent excluded constituencies as spectacles within normalising discourses. Consequently, two frameworks and representations of arts practices by excluded constituencies are explored, one “high” art by “outsiders”, the other a more functional welfare orientated art by those with mental health problems.